De-localizing brittle fracture. (September 2021) - Salman, O.U.; Truskinovsky, L.
Abstract: Extreme localization of damage in conventional brittle materials is the source of a host of undesirable effects. We show how artificially engineered metamaterials with brittle constituents can be designed to ensure that every breakable sub-element fails independently. The main role in the proposed design is played by high contrast composite sub-structure with zero-stiffness, furnishing nonlocal stress redistribution. The ability to de-localize cracking in such nominally brittle systems can be linked to the fact that their continuum description is dominated by the gradient (bending) rather than classical (stretching) elasticity. By engineering a crossover from brittle to effectively ductile (quasi-brittle) behavior, we reveal the structural underpinning behind the difference of fracture and damage.